Radiation Diagnosis and Therapy of Vertebral Hemangiomas - S. A. Mizyurov; V. V. Zaretskov; S. V. Likhachev; A. V. Zaretskov; K. K. Levchenko; V. B. Arsenievich; S. I. Kireev; D. Yu. Sumin (Вестник рентгенологии и радиологии)
The literature review is devoted to the current radiation methods for studying vertebral hemangiomas. The significance of basic (radiography, computed tomography, and magnetic resonance imaging) and additional (Doppler ultrasound, scintigraphy, and selective angiography) diagnostic techniques is analyzed and their role in determining the indications for surgical treatment is clarified. The priority of computed tomography over other imaging methods for this pathology is established. The use of radiation therapy for vertebral hemangiomas at the present stage of medicine development is highlighted.